CORRELATION BETWEEN CRYSTAL STRUCTURE AND RESISTIVITY OF HIGH-TEMPERATURE SUPERCONDUCTING CUPRATES - H. P. Roeser; Bohr, A.; Haslam, D. T.; J. S. Lόpez; M. Stepper; F. M. Hube; A. S. Nikoghosyan
The experimental resistivity of high-temperature superconducting (HTSC) cuprates at about Tc has been determined by many authors. For large devices the in-CuO2-plane resistivity has a range of ~0.5 < r(exp) < 1.5*10^-6 Ω m. Above Tc all HTSC materials behave like a classical device and the resistance depends on cross section and length of the device. Assuming a superconducting unit volume and a mode structure, which are given by the doping pattern throughout the whole crystal, the experimental resistivity values have been plotted versus ~LR/Nmode. A strong linear correlation in the form r(exp)=m3*(LR/Nmode)*(n4/n3)can be seen with a slope of m3=(13.39+_0.79)*10^3 Ω. LR is an effective resistivity length, Nmode is the number of CuO2 planes per unit cell, n3 is the number of Cu3+-ions per chemical formula and n4 is the number of different shifted stacking sequences per unit cell. The investigation has only been performed for a maximum of Nmode=4 modes. The value for m3 is very close to the fundamental resistance of a single-mode ballistic conductor Rsm=h/2e^2=12.906 Ω, which appears when size quantization plays a dominant role.
Keywords: Physics; Superconductivity